Investigating The Relationship Between Motor Skills and Physical Activity Levels of The Children at 8-10 Years of Age - Zait Burak Aktuğ; Rüçhan İri (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to determine the physical activity level (PAL) and motor skill (MS) of children aged 8-10 years and investigate the relationship between MS, PAL and Body Mass Index (BMI). 126 female and 119 male voluntary children aged 8-10 years participated in the study. PAL for the subjects who participated in the study was determined by the Physical Activity Questionnaire for Older Children (PAQ-C), Gross Motor Skills (GMS) as the total value of object control (OC) and loco-motor skills (LOCO) was determined via Test of Gross Motor Development (TGMD-2), and the BMI of the subjects was determined by means of the formula; the weight kg is divided by the height in square meter [weight (kg)/height (m2)]. Pearson Correlation Analysis was used to determine the relationships among PAL, BMI and MS. It was found that there was a negative relationship between female subjects’ BMI and MS. As PAL levels of male subjects increase, LOCO skills also increase, whereas as the PAL of female subjects increases, their OC skills increase. Moreover, the differences between the genders may have an effect on the types of activities in which children participate. Considering that MSs have played significant roles upon physical structure and psychological mood of the individuals throughout their childhood and the rest of their life. As a conclusion, it is likely to mention that in order to develop both MS and PAL, guiding children towards physical activity is significant.